Implementasi Pendataan Kawin Belum Tercatat : Solusi Melalui Aplikasi Kalimasada untuk Peningkatan Kualitas Data Penduduk di Kelurahan Kedungdoro - Fawaid Asad; Yusuf Hariyoko (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Community Service in English means community service, which is an activity of helping the community in the form of several activities without expecting any form of reward. Community service is one of the pillars of the Tri Dharma of Higher Education, namely: education, research and community service. Universities not only carry out education for their students, but also carry out research and develop innovation, as well as preserve and develop superior knowledge that is beneficial to society. Data collection on marriages that have not been registered is a problem that is often faced in managing population data in many sub-districts. This article discusses the proposed solution through the development of the Kalimasada application to improve the quality of population data in Kedungdoro Village. The service method used involves the process of data collection, needs analysis, application development, and user training. The approach used is the use of mobile application-based information technology to facilitate the process of collecting data on unregistered marriages. The Kalimasada application is designed with an intuitive and easy-to-use interface, allowing sub-district officials to quickly record data on unregistered marriages. In addition, this application is equipped with an automatic data validation feature to reduce input errors and increase data accuracy. During the service process, training was conducted for the community about the importance of reporting unregistered marriages to subdistrict officers via the Kalimasada application. The results of implementing the Kalimasada application show a significant increase in data collection on unregistered marriages in Kedungdoro Village. With this application, the data collection process becomes more efficient and accurate, producing more valid and reliable data. Apart from that, public participation in reporting unregistered marriages has also increased, so that the data collected becomes more complete. In conclusion, developing the Kalimasada application is an effective solution for improving the quality of population data in Kedungdoro Village. The use of information technology in public administration can help speed up the data collection process and increase data accuracy. The next step is to expand the implementation of this application to other sub-districts and continue to carry out monitoring and evaluation to ensure its sustainability and effectiveness in the long term.